Occupational risk management with a focus on University Social Responsibility: a study from teachers’ perspectives - Flores Montenegro, Isela; Gómez Romero, José Gerardo Ignacio; Marceleño Flores, Susana María Lorena (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To evaluate the perception of teaching staff regarding University Social Responsibility (USR) practices and their relationship with strengthening occupational risk management in a higher education institution. MATERIAL AND METHOD: The research is a mixed-method, descriptive approach. It also included the application of a questionnaire based on the URSULA model to a random sample of 130 teachers, as well as the development of an occupational risk matrix based on ISO 31000 and ISO 45001 standards, using the IPERC methodology. RESULTS: Faculty members positively perceive USR initiatives, highlighting the organizational management dimension as the most influential in their assessment, with positive work environment and equity being the highest-rated aspects. Twenty-six occupational hazards associated with the institution’s activities were identified, and areas of opportunity for integrating USR into risk management were analyzed. CONCLUSIONS: This study shows that faculty’s favorable perception of USR can strengthen occupational risk management. Although the URSULA model does not directly assess risks, it has identified factors such as work environment, ethics, and equity that, when integrated with the technical diagnosis based on ISO 31000 and ISO 45001 standards, contribute to building safer, more sustainable work environments aligned with responsible institutional management.